Exact Mediation Analysis for Ordinal Outcome and Binary Mediator. Issue 6 (5th October 2022) - Stanghellini, Elena; Kateri, Maria
Abstract : With reference to a single mediator context, this brief report presents a model-based strategy to estimate counterfactual direct and indirect effects when the response variable is ordinal and the mediator is binary. Postulating a logistic regression model for the mediator and a cumulative logit model for the outcome, we present the exact parametric formulation of the causal effects, thereby extending previous work that only contained approximated results. The identification conditions are equivalent to the ones already established in the literature. The effects can be estimated by making use of standard statistical software and standard errors can be computed via a bootstrap algorithm. To make the methodology accessible, routines to implement the proposal in R are presented in the eAppendix; http://links.lww.com/EDE/B962 . We also derive the natural effect model coherent with the postulated data-generating mechanism.